The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5937/istrped2201147p
|View full text |Cite
|
Sign up to set email alerts
|

Analysi̇s of li̇fe sati̇sfacti̇on level of uni̇versi̇ty students usi̇ng hi̇erarchi̇cal li̇near modeli̇ng

Abstract: Life satisfaction is among the basic components which demonstrate that individuals can lead a quality life. Many intertwined factors affect individuals' life satisfaction. Analyzing these factors at different levels will allow the analysis results to be more significant. This study aimed to reveal the effects of variable at the student and department level that will affect the life satisfaction level of university students, using the Hierarchical Linear Modeling. In addition, the study aimed to reveal which va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Another study discovered that parental support, rather than parental control or autonomy giving, influences adolescent life happiness over time (Saha et al, 2010). In terms of life satisfaction based on different faculties, a study revealed that the life satisfaction ratings of university students vary among departments, with 13% attributed to inter-departmental variations and 87% attributed to intra-student variations (Pekdogan & Yurtçu, 2022). A study 10.54392/ajir2413 conducted in India revealed that the marital status of individuals is a notable demographic factor that significantly impacts the level of life satisfaction among students (Khera, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Another study discovered that parental support, rather than parental control or autonomy giving, influences adolescent life happiness over time (Saha et al, 2010). In terms of life satisfaction based on different faculties, a study revealed that the life satisfaction ratings of university students vary among departments, with 13% attributed to inter-departmental variations and 87% attributed to intra-student variations (Pekdogan & Yurtçu, 2022). A study 10.54392/ajir2413 conducted in India revealed that the marital status of individuals is a notable demographic factor that significantly impacts the level of life satisfaction among students (Khera, 2022).…”
Section: Introductionmentioning
confidence: 99%